Body mass index in patients with moderate‐to‐severe psoriasis in Spain and its impact as an independent risk factor for therapy withdrawal: results of the Biobadaderm Registry. (15th July 2013) - Carrascosa, J.M.; Vilavella, M.; Garcia‐Doval, I.; Carretero, G.; Vanaclocha, F.; Daudén, E.; Gómez‐García, F.J.; Herrera‐Ceballos, E.; De la Cueva Dobao, P.; Belinchón, I.; Sánchez‐Carazo, J.L.; Alsina, M.; et al.
Abstract Background There are few data on the prevalence of obesity in the general psoriasis population and on the real impact of obesity on the management of psoriasis patients in the clinical setting. Objectives To evaluate the prevalence of overweight and obesity in patients with moderate‐to‐severe psoriasis compared to the general population and to assess the relationship between Body Mass Index (BMI) and the risk of discontinuing treatment. Methods Patients registered on Biobadaderm, a prospective registry, were grouped according the different categories of BMI and compared to the general Spanish population. Drug survival was analysed considering only drug withdrawal due to lack of effectiveness, remission and adverse events. Results A total of 1162 moderate‐to‐severe psoriasis patients on systemic conventional or biological treatment were recruited. The prevalence of obesity was found to be significantly higher in psoriasis patients than in the general Spanish population (P < 0.001). In multivariate analysis a 5‐unit increase in BMI, similar to a change in BMI category from normal weight to overweight and from overweight to obesity, was associated with a 12% increased risk of discontinuing therapy due to lack of effectiveness (HR 1.12, 95% CI: 1.01–1.24) and with a 17% increased risk of having an adverse event (HR 1.17, 95% CI: 1.02–1.36), both independently of the drug used. Conclusions Patients with moderate‐to‐severe psoriasis had a higher prevalence of obesity than the general population. Increased BMI was associated with an increased risk of treatment discontinuation due to lack of effectiveness and a higher risk of adverse events.